MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN MELALUI MODEL COOPERATIF LEARNING TIPE JIGSAW DI KELAS IV SD - Yulia, Risya (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This study originated from the reality on the ground that the teacher teaching less attractive to students due to the teacher-centered learning is that students become bored. Therefore, researchers wanted to improve learning in this study using the Jigsaw cooperative learning model type that aims to improve the learning process and learning outcomes Civics fourth grade students in District 04 District Sikabu Lubuk cone.This study used qualitative and quantitative approaches. In using the Jigsaw cooperative learning model students are placed on the type of learning groups beranggotan 4 to 6 students which is a mixture of different academic abilities so that in each group there are students who are high achievers, moderate, low-san. The steps Jigsaw cooperative learning types are: provision of information, the establishment of the original group of 4-6 people, the establishment of an expert group, discussion group of experts, the provision of information to members of the original group, the percentage of the class, quizzes / evaluations, awards groups.Based on the results of research using the Jigsaw cooperative learning model type on the learning process Civics Class IV Elementary School District 04 Sikabu Lubuk cone can be seen in the percentage of students completeness Cognitive aspects of the first cycle 71,% increase on the second cycle to be 81.75%, affective aspects of the cycle I 74 , 17% increase in cycle II to 87.50%, and psychomotor aspects of 77.08% in the first cycle to the second cycle increased to 90%. To obtain the recapitulation in the first cycle value of 74.08, while in the second cycle 86.41 Thus Jigsaw cooperative learning model types can be used in class IV Elementary School District 04 Sikabu Lubuk cone. Kata kunci: hasil belajar, PKN, cooperatif learning tipe jigsaw